2012
DOI: 10.1108/00220411211239057
|View full text |Cite
|
Sign up to set email alerts
|

Modelling information‐seeking behaviour of graduate students at Kuwait University

Abstract: PurposeThis paper seeks to report the results of research conducted to model the information‐seeking behaviour of graduate students at Kuwait University and the factors influencing that behaviour.Design/methodology/approachThe research employed a number of different approaches: a questionnaire survey to 800 graduate students studying at Kuwait University; a questionnaire survey to 180 academics at the university; semi‐structured interviews with eight academics; face‐to‐face and online interviews with 11 univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 36 publications
2
24
0
1
Order By: Relevance
“…Al Muomen et al, 2012). This is also consistent with studies in many other countries which have identified such misperceptions among library users about librarians and libraries, and particularly a lack of awareness of librarians' role, duties and skills (Bickley & Corrall, 2011;Fagan, 2003;Gardner & Eng, 2005;Majid & Haidar, 2008).…”
Section: Kuwaiti Education and Librarians' Statussupporting
confidence: 77%
See 1 more Smart Citation
“…Al Muomen et al, 2012). This is also consistent with studies in many other countries which have identified such misperceptions among library users about librarians and libraries, and particularly a lack of awareness of librarians' role, duties and skills (Bickley & Corrall, 2011;Fagan, 2003;Gardner & Eng, 2005;Majid & Haidar, 2008).…”
Section: Kuwaiti Education and Librarians' Statussupporting
confidence: 77%
“…Al-Muomen, Morris and Maynard (2012) are rather more optimistic about lecturers' understanding of the importance of the library, though confirm a lack of collaboration between them and librarians. As regards technology in academic libraries in Kuwait as such, research is still in its infancy, reflecting also the relative recency of the emergence of an academic system.…”
Section: ) Thatmentioning
confidence: 99%
“…Thus, the study described the information seeking process as consisting of many steps: recognizing information needs, trying to fulfill the need by formulating the problem, expressing the information need using a search system, examining the results, reformulating the problem, and using the results. Al-Muomen et al (2012) proposed a model of the information seeking behavior of Kuwaiti undergraduate students. The model adopted the findings of Rowley and Urquhart (2007) to understand undergraduates' information-seeking behavior and revealed that all the factors adopted, such as "identifying need, locating sources, searching" affected students' information behavior.…”
Section: Information Behavior Modelsmentioning
confidence: 99%
“…The overarching aim of the study is to establish an understanding of the scholarly communication practices of Arab social science and humanities scholars. Previous studies that explored the scholarly publishing and information‐seeking behaviour of Arab scholars concluded that scholarly practices may differ among them (Al‐Muomen, Morris, & Maynard, ; Al‐Suqri, ; Al‐Wreikat, Rafferty, & Foster, ; Elgllab & Shehata, ). Understanding the scholarly communication behaviour of Arab scholars may lead to a better understanding of research practices in Arab countries.…”
Section: Introductionmentioning
confidence: 99%